2020
DOI: 10.1029/2019wr026087
|View full text |Cite
|
Sign up to set email alerts
|

Applying ADCPs for Long‐Term Monitoring of SSC in Rivers

Abstract: The flow rate and the suspended sediment concentration (SSC) of two different rivers draining into the Adriatic Sea basin, the Secchia in Italy and the Devoll in Albania, were analyzed by processing the data collected in a 245-day period at monitoring stations equipped with side-looking acoustic Doppler current profilers (H-ADCPs). SSC was determined as a by-product of the echo profiles along the horizontal aligned acoustic beams emitted by H-ADCPs. For the first time, the effect of organic matter other than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…We could wonder whether organic suspended particles might also explain the uncertainties of existing models in rivers (Aleixo et al., 2020) and consider organic content quantification. Nevertheless, it was considered as negligible in this experiment as concentration in sediment particles was high and the ratios of density and compressibility way lower for organic particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could wonder whether organic suspended particles might also explain the uncertainties of existing models in rivers (Aleixo et al., 2020) and consider organic content quantification. Nevertheless, it was considered as negligible in this experiment as concentration in sediment particles was high and the ratios of density and compressibility way lower for organic particles.…”
Section: Discussionmentioning
confidence: 99%
“…Method 3 uses the ratio of attenuation to backscatter at only one frequency; 0 ( ) a  θ is estimated. Such a method was also applied by Guerrero and Di Federico (2018) and Aleixo et al (2020).…”
Section: 1029/2021wr029589mentioning
confidence: 99%
“…Although it may be assumed that suspended matter is easier to quantify as a result of its more homogeneous transport mode (convection and diffusion) compared with bedload (stochastic behaviour) (Muste et al, 2016), mainly direct measurement methods, with limited spatial and temporal resolution, are used in practice. However, indirect methods are becoming more common, for example based on optics (e.g., turbidity meters or devices based on laser diffraction; Ankers et al, 2003;Czuba et al, 2015;Haun et al, 2015;Minella et al, 2008) or acoustics (acoustic Doppler current profilers, ADCPs), and these can enable higher spatial and temporal resolution (Aleixo et al, 2020;Baranya & J ozsa, 2013;Ehrbar et al, 2017;Haun & Lizano, 2018;Guerrero & Di Federico, 2018;Guerrero et al, 2016Guerrero et al, , 2017Latosinski et al, 2014). However, processes such as flocculation or the occurrence of organic content within the water column influence not only the behaviour of transported particles but also the measurements themselve, when based for example on optics (Haun et al, 2015).…”
Section: Sediment Transport Processesmentioning
confidence: 99%
“…The physical, chemical and biological interaction among SS components changes the structure (dis‐/aggregation) and properties of SS such as particle size, density and composition (Maggi & Tang, 2015), and might result in flocculation (Spearman et al., 2011). These interactions are also influenced by meteorological, hydrological, ecological and anthropogenic pressures (Aleixo et al., 2020; Ankers et al., 2003). Recent studies showed that information on SS size and composition, also considered as primary floc characteristics, is important in physics‐based modeling studies (e.g., Grangeon et al., 2012; Lepesqueur et al., 2019; Manning et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These sampling techniques are time‐consuming, which make high frequency measurements impractical (Druine et al., 2018). Limited accessibility to stream sampling locations during turbulent conditions or high flows, when the largest amount of sediment is transported downstream, also introduces measurement uncertainty (Aleixo et al., 2020). Furthermore, transformation or breaking of SS flocs might occur during refrigeration and transportation to the laboratory for ex situ analysis (Gałuszka et al., 2015).…”
Section: Introductionmentioning
confidence: 99%